Development of reference assignment in children: a direct comparison to the performance of cognitive shift - Murakami, Taro; Hashiya, Kazuhide (Frontiers in Psychology, 2014)
The referent of a deictic embedded in a particular utterance or sentence is often ambiguous. Reference assignment is a pragmatic process that enables the disambiguation of such a referent. Previous studies have demonstrated that receivers use social-pragmatic information during referent assignment; however, it is still unclear which aspects of cognitive development affect the development of referential processing in children. The present study directly assessed the relationship between performance on a reference assignment task (Murakami & Hashiya, 2014) and the Dimensional Change Card Sort (DCCS) task in three- and five-year-old children. The results indicated that the performance of the 3-year-olds in an event that required an explicit (cognitive) shift was associated with DCCS performance; however, this was not observed in the 5-year-olds, possibly due to a ceiling effect. Thus, while the development of skills that mediate cognitive shifting might adequately explain the explicit shift of attention in conversation, the pragmatic processing underlying the implicit shift, which requires reference assignment, might follow a different developmental course.